Archaeoentomological Perspectives on Dorset Occupations in Newfoundland: A Case Study from the Site of Phillip’s Garden (EeBi-1) - Dussault, Frédéric; Bell, Trevor J.; Grimes, Vaughan (ARCTIC, 2017)
The Dorset Paleo-Inuit occupied the island of Newfoundland for over 800 years (1990 BP to 1180 BP), producing a unique and identifiable archaeological record. Despite this, our current understanding of this sea-mammal hunting population is essentially based on past analysis of architecture, artefacts, and animal remains. While these data show that the Dorset intensively used sites at different locations through the Arctic and Subarctic, very little information is known regarding their impact on their surroundings and the environment. Our research is based on soil samples collected at the site of Phillip’s Garden, which is considered to be one of the most intensely occupied sites within the Dorset culture’s geographic range. Beetles, which are known to be ecological specialists, were used as a proxy in this research in order to document the composition and fluctuation in vegetation, and environmental change through time at the site. The analysis demonstrates that the Dorset communities of Phillip’s Garden harvested trees, and modified the environment and the flora surrounding their settlement more intensively than previously thought. Entre 1990 AA et 1180 AA, l’île de Terre-Neuve a connu une période d’occupation de plus de 800 ans par la culture dorsétienne. Cette occupation, documentée dans les données archéologiques, a laissé des traces uniques et visibles. Malgré cette richesse archéologique laissée par les Dorsétiens, notre compréhension de cette culture axée sur la chasse aux mammifères marins est principalement basée sur les données architecturales, artéfactuelles et zooarchéologiques. Ces données ont permis de démontrer que la culture dorsétienne a occupé de façon très intensive plusieurs sites localisés dans l’Arctique et le Subarctique. Cependant, peu d’informations sont fournies par ces données quant à l’impact de cette culture sur son environnement et ses lieux d’occupation. Les données utilisées au cours de notre recherche ont été récupérées dans des échantillons de sols ayant été prélevés sur le ...